ISLAMIC EDUCATION WITHIN THE RELIGIOUS SOCIAL ORGANIZATION NAHDLATUL ULAMA - Muhdir; Moh. Roqib (International Journal of Teaching and Learning, 2026)
This study aims to describe the concept of Islamic education as envisioned by Nahdlatul Ulama (NU), its contribution to the national education system, and the challenges and prospects it faces in the modern era. The research adopts a qualitative-descriptive method based on library research, using content analysis of relevant literature. The findings reveal that NU plays a vital role in advancing Islamic education through its network of pesantren (Islamic boarding schools), madrasahs, and universities that integrate the values of Ahlussunnah wal Jama’ah, such as moderation, tolerance, and balance. Despite facing challenges related to digital transformation and infrastructure disparities, NU holds significant potential in strengthening an inclusive and contextualized model of Islamic education in Indonesia.